Asymmetries in the responses of regional job flows to oil price shocks - Karaki, Mohamad B. (2017)
This paper studies the effect of oil price innovations on manufacturing job flows across U.S. states. First, I estimate a nonlinear structural equation model and compute impulse response functions by Monte Carlo integration. I find asymmetries in the responses of job flows to positive and negative oil price innovations. Yet, these asymmetries do not pass a test of symmetry on the impulse responses, especially after accounting for data mining. Third, I use a test for the absence of job reallocation to evaluate whether an unexpected increase in the real price of oil price triggers an important change in job reallocation. I find that oil price shocks have limited regional allocative effects. (JEL E24, E32, Q43)